Compliment responses in the drama “Twenty Five Twenty One” (스물 다섯 스물 하나) : pragmatic studies - Disha Aulia Fatikha (Journal of Korean Applied Linguistics, 2023)
Without even realizing it, language is a common tool we employ in social interactions to interact and communicate. This suggests that humans communicate with one another through language. This research aims to find a compliment response to the drama "Twenty-One Twenty-Five. In this drama, "Twenty-Five Twenty-One," found that there is a compliment response between the characters. Based on Herbert's compliment, responses are divided into 12 forms Appreciation Token, Comment acceptance, Praise Upgrade, Comment history, Reassignment, Return, Scale Down, Question, Disagreement, Qualification, No Acknowledgement, and Request Interpretation. This research used Herbert's compliment responses theory to identify compliment responses from dialogue characters in the drama “Twenty-Five Twenty-One”. This research uses data from dialogue characters in the drama "Twenty-One Twenty-Five” and qualitative method. Next, Simak and Padan's methods were used to identify compliment responses. After collecting compliment response data from the characters’ dialogue, compliment responses are analyzed by implementing a descriptive way. After analyzing compliment response data, the results found that of the 12 praise responses put forward by Herbert, there were 9 compliment responses in the drama. These are Appreciation token, Comment Acceptance, Praise Upgrade, Comment History, Return, Scale Down, Question, Disagreement, and also No Acknowledgement. Korean people tend to respond to compliments not only by saying "감사합니다 (gamsahamnida)" or "고마워 (gomawo)", but also use another expression to respond to some compliments, such as a smile or the person is accepting the compliment, but adding some comment.